Shoulder season controls on methane emissions from a boreal peatland - Jentzsch, Katharina; Männistö, Elisa; Marushchak, Maija E.; Korrensalo, Aino; van Delden, Lona; Tuittila, Eeva-Stiina; Knoblauch, Christian; Treat, Claire C. (Biogeosciences, 2024)
Cold-season emissions substantially contribute to the annual methane budget of northern wetlands, yet they remain underestimated by process-based models. Models show significant uncertainty in their parameterization of processes, particularly during the transitional phases of freezing and thawing temperatures in the shoulder seasons. Our aim was to identify the environmental controls on the components of the methane fluxes – methane production, oxidation, and transport – from a boreal peatland during the shoulder seasons. We partitioned net methane emissions into their components by combining manual chamber flux measurements on vegetation removal treatments with pore water sampling for concentrations and stable carbon isotope ratios of dissolved methane in the wet hollows of Siikaneva bog in southern Finland during seasonal field campaigns in 2021 and 2022. The results suggest that the decrease in methane emissions due to decreasing production rates with decreasing peat temperatures in the shoulder seasons was dampened by several processes. Firstly, highly efficient transport of methane through the aerenchyma of peatland sedges continued outside of the growing season after plant senescence. Secondly, decaying vascular plants provided additional substrate for methane production at the end of the growing season. Thirdly, accumulation of methane in the pore water partly delayed the emission of methane produced in summer and winter to the shoulder seasons. Substrate-limited oxidation rates, however, largely compensated for the higher diffusion rates related to high pore water concentrations in fall. Accounting for these processes specific to the shoulder seasons by separately modeling the components of methane fluxes will likely work against the underestimation of cold-season methane emissions from northern peatlands.